Cooperación Sur-Sur entre Brasil y Ecuador: análisis del fortalecimiento y consolidación de las capacidades técnicas de gestión de la Red Ecuatoriana de Bancos de Leche Humana durante el período 2015-2017. - Reyes Perez, Jeanette Aracelly (2019)
The paper presented here analyzes the strengthening and consolidation of the technical skills of the work done by the Ecuadorian Network of Human breastmilk Banks during the period of time between the years 2015 to 2017 in the South-South Brazil-Ecuador Cooperation context. Employing as theoretical framework the South-South Cooperation and constructivists theory. The methodology has being made through qualitative research, supported with data recollection such as: first and second hand documentary sources, and semi-structured interviews, mainly to the officials of the human breastmilk banks in cities of Quito and Ambato. The first chapter showcases conceptual approaches towards the concepts of International Health, Global Health and Diplomacy Health references, followed up by the growth and evolution of the South-South Cooperation. The second chapter showcases the most known public institutions from Ecuador and Brazil linked in matters of breast milk cooperation. The third chapter speaks about the improvements that can be done and are necessary to programs like the ones mentioned above